Instruments for patient education: Psychometric evaluation of the expected knowledge (EKHP) and the received knowledge of hospital patients (RKHP) - Leino-Kilpi, Helena; Inkeroinen, Saija; Cabrera, Esther; Charalambous, Andreas; Fatkulina, Natalja; Katajisto, Jouko K.; Sigurdardottir, Árún K.; Sourtzi, Panayota; Suhonen, Riitta A.; Zabalegui-Yárnoz, Adelaida; Valkeapää, Kirsi (My University, 2020)
Purpose: In patient education, there is a need for valid and reliable instruments to assess and tailor empowering educational activities. In this study, we summarize the process of producing two parallel instruments for analyzing hospital patients’ expectations (Expected Knowledge of Hospital Patients, EKhp) and received knowledge (Received Knowledge of Hospital Patients, RKhp) and evaluate the psychometrics of the instruments based on international data. In the instruments, six elements of empowering knowledge are included (bio-physiological, functional, experiential, ethical, social, and financial). Patients and Methods: The original Finnish versions of EKhp and RKhp were tested for the first time in 2003, after which they have been used in several national studies. For international purposes, the instruments were first translated into English, then to languages of the seven participating European countries, using double-checking procedure in each one, and subsequently evaluated and confirmed by local researchers and language experts. International data collection was performed in 2009–2012 with a total sample of 1,595 orthopedic patients. Orthopedic patients were selected due to the increase in their numbers, and need for educational activities. Here we report the psychometrics of the instruments for potential international use and future development. Results: Content validities were confirmed by each participating country. Confirmatory factor analyses supported the original theoretical, six-dimensional structure of the instruments. For some subscales, however, there is a need for further clarification. The summative factors, based on the dimensions, have a satisfactory internal consistency. The results support the use of the instruments in patient education in orthopedic nursing, and preferably also in other fields of surgical nursing care. Conclusion: EKhp and RKhp have potential for international use in the evaluation of empowering patient education. In the future, testing of the structure is needed, and validation in other fields of clinical care besides surgical nursing is especially warranted.
Keywords: Empowerment; Nursing; Patient education as topic; Patient participation; Patient-centered care; Surveys and questionnaires